THE INFLUENCE OF PRODUCT QUALITY, PROMOTION AND DESIGN ON THE PURCHASE DECISION OF YAMAHA MIO MOTOR VEHICLES - Purwanto purwanto (Jurnal Ekonomi, 2021)
A person's buying behavior towards a product is influenced by many factors. Each individual has different desires and tastes. Product quality is a very influential factor in purchasing decisions, besides that there are many other factors that influence the buying behavior. This study aims to analyze the effect of product quality, promotion and design on purchasing decisions for Yamaha Mio motorcycle products and analyze the variables that have the most dominant influence on purchasing decisions for Yamaha Mio motorcycle products in the community in the Surakarta area. From the results of the classical assumption analysis, the normality test with the Kolmogorov-Smirnov obtained is significantly greater than 0.05, which means that the data distribution is normal. Multicollinearity test obtained VIF and Tolerance values ​​that are close to one so that it can be concluded that the regression model has no multicollinearity problem, while the heteroscedasticity test using the Glejser method states that there is no problem. Based on the results of multiple linear regression analysis from the t test, it was found that partially product quality had a significant effect on purchasing decisions for Yamaha Mio motorcycle products, while promotion and design had a significant effect on the 5% level. From the results of the F test that simultaneously product quality, promotion and design have a significant effect on purchasing decisions for Yamaha Mio motorcycle products where the value of F count > F table. Product quality has the most dominant influence on purchasing decisions for Yamaha Mio motorcycle products. The R square value is 0.255,